Radiation-induced ferroptosis via liposomal delivery of 7-Dehydrocholesterol - Jianwen Li; Shuyue Zhan; Wei Yang; He Zhang; Xinrui Ma; Fanghui Chen; Amy Li; Pakteema Tong; Fangchao Jiang; Zhengwei Cao; Ian Delahunty; Jiayi Wang; et al. (Journal of Nanobiotechnology)
Abstract Background Ferroptosis is an emerging cell death mechanism characterized by uncontrolled lipid peroxidation. However, selectively inducing ferroptosis in cancer cells remains a challenge. Methods We explore an approach that enables ferroptosis induction through external radiation. The key component of this technology is 7-dehydrocholesterol (7DHC), a natural biosynthetic precursor of cholesterol. To facilitate delivery, we demonstrate that 7DHC, like cholesterol, can be incorporated into the lipid layer of liposomes. To enhance targeting, we also introduced NTSmut, a ligand for the neurotensin receptor 1 (NTSR1), which is overexpressed in multiple malignancies, into liposomes. Results Under radiation, 7DHC reacts with radiation-induced reactive oxygen species (ROS), initiating a radical chain reaction with polyunsaturated fatty acids (PUFAs) in cell membranes. This process results in direct lipid peroxidation and subsequent ferroptotic cell death. In vivo studies demonstrate that NTSmut-conjugated, 7DHC-loaded liposomes (N-7DHC-lipos) effectively accumulate in tumors and significantly enhance the efficacy of radiation therapy. Conclusion While conventional radiosensitizers primarily target DNA and its repair mechanisms, our study introduces a strategy to enhance radiotherapy by specifically activating ferroptosis within the irradiated area, thereby minimizing systemic toxicity. Such a strategy of controlled activation of ferroptosis offers a favorable therapeutic index and potentially opens avenues for clinical application.